1997
DOI: 10.2337/diab.46.7.1235
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Novel Peripheral Action of Leptin as a Metabolic Signal to the Adrenal Gland: Leptin Inhibits Cortisol Release Directly

Abstract: The crucial role of glucocorticoids in obesity and insulin resistance and the actions of the OB protein leptin on the hypothalamic-pituitary-adrenal (HPA) axis suggest that there is an important interaction of leptin with the glucocorticoid system. Therefore, we designed a study to test the effect of leptin directly on adrenocortical steroidogenesis. Primary cultures of bovine adrenocortical cells were incubated with increasing concentrations (10-1,000 ng/ml) of recombinant mouse leptin for 24 h, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
0
11

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(119 citation statements)
references
References 36 publications
9
99
0
11
Order By: Relevance
“…The role of leptin as an adipostat is confirmed by the increases in plasma leptin levels (Table 4; P , 0.05) at the end of the restriction phase and when AA intake was reduced. The observation that leptin inhibits cortisol synthesis by adrenal cells (Bornstein et al, 1997;Pralong et al, 1998) is supported by the negative correlation observed in this experiment between plasma circulating leptin and cortisol (P , 0.01; r 5 20.74). In contrast, the observation that leptin increases GH plasma concentration (Barb et al, 1998) is supported by the positive correlation between plasma levels of the two hormones observed in this experiment (P , 0.01; r 5 0.81).…”
supporting
confidence: 70%
“…The role of leptin as an adipostat is confirmed by the increases in plasma leptin levels (Table 4; P , 0.05) at the end of the restriction phase and when AA intake was reduced. The observation that leptin inhibits cortisol synthesis by adrenal cells (Bornstein et al, 1997;Pralong et al, 1998) is supported by the negative correlation observed in this experiment between plasma circulating leptin and cortisol (P , 0.01; r 5 20.74). In contrast, the observation that leptin increases GH plasma concentration (Barb et al, 1998) is supported by the positive correlation between plasma levels of the two hormones observed in this experiment (P , 0.01; r 5 0.81).…”
supporting
confidence: 70%
“…In addition, administration of leptin in developing rats increases the expression of the glucocorticoid receptor in the PVN and hippocampus [51], presumably leading to increased sensitivity of the glucocorticoid receptor. On the other hand, the leptin receptor is present in the adrenal gland, and leptin treatment can directly inhibit basal and ACTH-stimulated cortisol release from adrenal gland in both humans and rodents [52,53]. Collectively, these data support the notion that leptin is capable of regulating the HPA axis at multiple levels.…”
Section: Impact Of Leptin On Hpasupporting
confidence: 60%
“…The latter indeed exerts a strong attenuating action on the hypothalamic-pituitary-adrenal axis 32 and was shown to directly inhibit cortisol release by bovine adrenocortical cells in primary culture. 33 The leptin-induced decrease in body weight was largely due to a reduction in fat, rather than lean mass, as suggested by the strong relationship between body weight and the sum of the two white adipose depots (r 0.95, P`0.0001) and the lack of effect of leptin on vastus lateralis weight. Comparable observations have been reported in lean and obese mice injected with leptin for 28 d. 7 There is substantial evidence that leptin reduces fat mass not only by reducing food intake, but also by stimulating thermogenesis.…”
Section: Discussionmentioning
confidence: 98%